Comparison of the transformation temperature, microstructure and magnetic properties of Co-Ni-Al and Co-Ni-Al-Cr shape memory alloys - Dagdelen, Fethi; Malkoc, Turkan; Kok, Mediha; Ercan, Ercan (Springer Heidelberg, 2016)
In this study, two-phase Co-Ni-Al shape memory alloys that have drawn attention recently due to their technological applications were investigated. Co-Ni-Al and Co-Ni-Al-Cr alloys were produced by melting method in an arc-melter furnace and physical properties between alloys were compared. At the end of experimental measurements it was observed that chromium addition did not change the crystal structure of the Co-Ni-Al alloy, but decreased the martensitic transformation temperature, the most significant property of shape memory alloys. Moreover, there was no significant change in the microstructure of the Co-Ni-Al alloy with chromium addition, and the presence of the two phases determined by X-ray analysis was also determined by optical microscopy. There was no significant change in micro hardness values of the alloys, while important changes in the magnetic properties were determined. It was observed that the Curie temperature decreased by approximately 500 degrees C with chromium addition and a considerable decrease in the magnetic saturation value was also determined.
Keywords: Martensitic-Transformation; Mechanical-Properties; Substitution